Delivery room management of very low birth weight infants in Germany, Austria and Switzerland - a comparison of protocols - Roehr CC; Gröbe S; Rüdiger M; Hummler H; Nelle M; Proquitté H; Hammer H; Schmalisch G (European Journal of Medical Research, 2010)
Abstract Background Surveys from the USA, Australia and Spain have shown significant inter-institutional variation in delivery room (DR) management of very low birth weight infants (VLBWI, < 1500 g) at birth, despite regularly updated international guidelines. Objective To investigate protocols for DR management of VLBWI in Germany, Austria and Switzerland and to compare these with the 2005 ILCOR guidelines. Methods DR management protocols were surveyed in a prospective, questionnaire-based survey in 2008. Results were compared between countries and between academic and non-academic units. Protocols were compared to the 2005 ILCOR guidelines. Results In total, 190/249 units (76%) replied. Protocols for DR management existed in 94% of units. Statistically significant differences between countries were found regarding provision of 24 hr in house neonatal service; presence of a designated resuscitation area; devices for respiratory support; use of pressure-controlled manual ventilation devices; volume control by respirator; and dosage of Surfactant. There were no statistically significant differences regarding application and monitoring of supplementary oxygen, or targeted saturation levels, or for the use of sustained inflations. Comparison of academic and non-academic hospitals showed no significant differences, apart from the targeted saturation levels (SpO2) at 10 min. of life. Comparison with ILCOR guidelines showed good adherence to the 2005 recommendations. Summary Delivery room management in German, Austrian and Swiss neonatal units was commonly based on written protocols. Only minor differences were found regarding the DR setup, devices used and the targeted ranges for SpO2 and FiO2. DR management was in good accordance with 2005 ILCOR guidelines, some units already incorporated evidence beyond the ILCOR statement into their routine practice.